### Author Topic: Chapter 5.3 Problem 1.1  (Read 2519 times)

#### Zicheng Ding

• Jr. Member
• Posts: 9
• Karma: 1
##### Chapter 5.3 Problem 1.1
« on: March 13, 2022, 02:32:37 PM »
For this problem we have the following equations: $u_{xx} + u_{yy} = 0 \space \space (-\infty < x < \infty , y > 0)$ and $u|_{y=0} = f(x)$.
After doing the Fourier Transformation, the equations become $\hat{u}_{yy} - k^2\hat{u} = 0$ and $\hat{u}(k,0) = \hat{f}(k)$.
In my understanding, we should get a general form as $\hat{u}(k,y) = A(k)e^{ky} + B(k)e^{-ky}$ and drop the first term if $k>0$ since as $y \rightarrow \infty$ the term $e^{ky} \rightarrow \infty$, and if $y<0$ we drop the second one.
On the answer provided by Prof. Kennedy it said $\hat{u}(k,y) = \hat{f}(k)e^{-k|y|}$, so I am a little confused since $\hat{u}(k,y) = \hat{f}(k)e^{-|k|y}$ makes more sense to me.

#### Victor Ivrii

• Elder Member
• Posts: 2607
• Karma: 0
##### Re: Chapter 5.3 Problem 1.1
« Reply #1 on: March 13, 2022, 04:19:38 PM »
You are right, it was a misprint